HYDRAULIC PISTON ENGINE WITH CRANKSHAFT MECHANISM - Duhanets , V.I.; Pukas , V.L.; Maisus , V.V.; Oleksijko , S.L. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The schematic diagram and the operation of a hydraulic piston engine with a crank and connecting rod mechanism is described, which contains a power cylinder with a housing and end flanges, a piston separating the cylinder into the first and second cavities, a crank and connected rod mechanism connected to the piston distributor with spool, discharge and drain channels connecting it to the first and second cavities, a tank with working fluid and a pump with a bypass valve. In addition to the piston, a stock affiliated to the spool is connected to the piston through one end, and a third flange is installed in the second cavity with the formation of a third cavity connected between it and the piston. Additionally, in the first cavity is installed the first, and in the third cavity - the second hydraulic reinforcing mechanisms, made in the form of axial flanges, rigidly connected through diametrically arranged radial axial rods with a cylinder body with holes in their joints. The flanges are connected by cylindrical sleeves with internal pistons placed inside, connected by rigid rods, the piston of the first cavity on one side, and the third cavity - on the second side of the piston. The third cavity is connected to the discharge and drain channels of the distributor, through which the third flange into the second cavity are two rods of the additionally installed lever-traction reinforcing mechanism connected to the piston and to the midpoints located in the second cavity, two levers, one end of which hinged to the body of the cylinder, and the second - connected to the connecting rod of the crank mechanism.